2000
DOI: 10.1016/s0304-3959(00)00293-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging in rats subjected to intense electrical and noxious chemical stimulation of the forepaw

Abstract: We examined whether cerebral activation to two different intense and painful stimuli could be detected using functional magnetic resonance imaging (fMRI) in alpha-chloralose anesthetized rats. Experiments were performed using a 9.4 T magnet and a surface coil centered over the forebrain. A set of gradient echo images were acquired and analyzed using our software based on fuzzy cluster analysis (EvIdent). Following the injection of 50 microl of formalin (5%) into the forepaw we observed a regional increase in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
59
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 45 publications
16
59
0
Order By: Relevance
“…This hypothesis could explain the difficulty of finding nociception-induced hemodynamic responses in the CPu in both humans and rodents (Casey, 1999;Tuor et al, 2000;Chang and Shyu, 2001;Farrell et al, 2005;Lowe et al, 2007), and a recent report of negative BOLD responses in the CPu induced by intense electrical stimulation to the rat forepaw (Zhao et al, 2008a). Moreover, consistent with our findings, Morrow et al reported that CBF was reduced during the early phase of formalin-induced pain (Morrow et al, 1998).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This hypothesis could explain the difficulty of finding nociception-induced hemodynamic responses in the CPu in both humans and rodents (Casey, 1999;Tuor et al, 2000;Chang and Shyu, 2001;Farrell et al, 2005;Lowe et al, 2007), and a recent report of negative BOLD responses in the CPu induced by intense electrical stimulation to the rat forepaw (Zhao et al, 2008a). Moreover, consistent with our findings, Morrow et al reported that CBF was reduced during the early phase of formalin-induced pain (Morrow et al, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…The noxious 60 V electrical stimulation of the rat forepaw with a pair of needle electrodes was quantified using a compound ammeter, which showed that the delivered current was ϳ15 mA. This current level is known to activate A␦ and C-fibers and induce nociception (Tuor et al, 2000;Chang and Shyu, 2001;Liu et al, 2004;Zhao et al, 2008b).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, hyperpolarized 129 Xe MRI showed patterns of brain activation consistent with those obtained using 1 H fMRI, using only a single set of images (one baseline and one post stimulus image) obtained from six animals. The magnitude of the signal difference between baseline and stimulus conditions for hyperpolarized 129 Xe (13-28%) was comparable to differences typically obtained with conventional BOLD fMRI (2 to 29%) (Bock et al, 1998;Silva et al, 1999;Mandeville et al, 1999;Tuor et al, 2000) using a rat forepaw activation paradigm.…”
Section: Experiments Results and Discussionsupporting
confidence: 73%
“…fMRI experiments using electrical stimulation in rats have repeatedly shown activations in the sensory motor cortex (1-3) and regions of the brain associated with processing of painful stimulation, such as the anterior cingulate (1). We wish to show that spinal fMRI can be used to assess electrical stimulation of the forepaw as well as capsaicin-induced pain in an anesthetized animal.…”
mentioning
confidence: 99%
“…THE OCCURRENCE OF BLOOD OXYGEN-LEVEL dependent (BOLD) contrast changes in the brain is well established (1)(2)(3)(4)(5)(6). Recently, the extension of functional magnetic resonance imaging (fMRI) from the brain to the spinal cord has been demonstrated (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%